Relationship Between Landscape Management, Land Use and Ecological Network in Nagykörű - Kutnyánszky, Virág; Szilvácsku, Zsolt Miklós (Journal of Environmental Geography, 2023)
In the summer of 2022, we experienced an extreme water shortage in the Great Hungarian Plain and the consequences influenced and still influence our lives in several ways. The long-term solution to the problem of drought is sustainable landscape management, which builds on the natural characteristics of the area – climate, soil, topography, hydrographic conditions and opportunities. The ecological network can provide a suitable framework for this concept, since the original idea intended to create balance between intensive and extensive land use. Our goal was to define the focus areas where the current cultivation is in conflict with the features of the landscape, and we identified the areas where it is necessary to change the cultivation method and those where other water retention proposals can gain space, thus ensuring water even in drier periods. The resulting land use will be in line with the water cycle, thereby increasing the area's resilience against drought. In our research, we chose the municipality of Nagykörű and its surroundings along the Tisza River as our study area, which - like the rest of the Great Plain - was hit by an exceptionally severe drought in the summer of 2022. On the 90 km2 research area, after fieldwork, we performed various GIS analyses. Based on these we examined the possibilities and suitability of the cultivation methods in the given area and worded our proposals. In the course of our research, we consulted with water management experts and local farmers in order to get a more accurate picture of the area's features, problems, and the feasibility of our proposals. The landscape architecture master students of MATE also helped us in preparing the analyses. The results showed that currently a significant part of the area is not managed in accordance with the geographical conditions. The deeper fields in the middle of the area, which currently are under intensive farming, would belo9ng, under natural conditions to the floodplain of the river Tisza. Here the extensive cultivation methods, such as orchards, gardens, or meadows are recommended. At the same time, the flood-free parts of the sample area are suitable for agriculture. If water retention strategies are used in the suitable areas, these will be more protected against the effects of drought.